Pengaruh Jumlah Simpanan Dan Tunggakan Kredit Terhadap Kesejahteraan Anggota Credit Union (Studi Kasus Pada Koperasi Kredit CU Lantang Tipo) - B61110025, SABINUS BENI (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT This study aims to determine how much influence the amount of savings and loan arrears to the welfare of members of the Credit Union . The model used in this study is a multiple regression model with the dependent variable is the welfare of members of the credit union , while the independent variable is the amount of savings and loan arrears . The data used in this study is primary data , where the data obtained and extracted from primary sources ( original source ) either in the form of qualitative data and quantitative data . The results showed an increase in the welfare of members after adanyan loan from CU Outspoken Tipo views of family expenses such as the cost of consumption , education and health costs as well as installment loans . Regression calculation results with the help of SPSS data processing program , or a pattern known to influence the relationship between Total Deposits ( X1 ) with CU Members Welfare Outspoken Tipo ( Y ) is positive , but the test results of unknown significance turns out that the X1 does not significantly affect Y. While Total Deposits ( X2 ) with CU Members Welfare Outspoken Tipo ( Y ) is positive . Keywords: Total Deposits, Delinquent Credit, Welfare, Credit Union